The interacting effects of prices and weather on population cycles in a preindustrial community. - Scott, S; Duncan, S; Duncan, C (1998)
The exogenous cycles and population dynamics of the community at Penrith, Cumbria, England, have been studied (1557-1812) using aggregative analysis, family reconstitution and time series analysis. This community was living under marginal conditions for the first 200 years and the evidence presented is of a homeostatic regime where famine, malnutrition and epidemic disease acted to regulate the balance between resources and population size. This provides an ideal historic population for an investigation of the direct and indirect effects of malnutrition. Throughout the period studied, a short wavelength oscillation in grain prices was apparently the major external factor that drove exogenous cycles in mortality, birth rate, and migration. In particular, the different responses of children to variations in food supply are emphasised; fluctuations in poor nutrition correlated significantly with the variations in mortality rates for infants (probably indirectly during pregnancy and directly during the first year of life) and for young children (via susceptibility to lethal infectious diseases). Migratory movements contributed to the maintenance of homeostasis in the population dynamics. A medium wavelength cycle in low winter temperatures was associated with a rise in adult mortality which, in turn, promoted an influx of migrants into this saturated habitat. A model incorporating these interacting associations between vital events and exogenous cycles is presented: grain prices were an important density-dependent factor and constituted the major component of the negative feedback of this population and drove the exogenous, short wavelength mortality cycles. Cycles of births and immigration provide a positive feedback for the build-up of susceptibles and the initiation of smallpox epidemics and increased population size.